Three- dimensional circular various weave patterns in woven preform structures - Bilişik, Kadir; Şahbaz Karaduman, Nesrin; Bilişik, Nedim Erman; Bilişik, Havva Esra (Sage Publications Ltd, 1 Olivers Yard, 55 City Road, London Ec1Y 1Sp, England, 2014)
The aim of this study was to develop three-dimensional (3D) fully interlaced representative circular woven preform structures and to understand the effects of weave pattern and number of layers on 3D circular woven structures. Various 3D circular woven preforms were developed. Data generated from these structures included yarn-to-yarn space, density, yarn angle, yarn length and crimp. It was shown that the weave patterns affected the 3D circular woven preform structures. The yarn-to-yarn spaces in the 3D fully interlaced circular structures were high compared to the traditional 3D orthogonal circular woven structures in fabric circumference (fabric outside surface) due to the interlacement of the yarn sets. The 3D plain, twill and satin structures resulted in axial angle (a) in fabric length; circumferential angle (c), and interlaced radial angle (ri) in fabric circumference and fabric diameter due to the axial-circumferential and axial-radial interlacements. The weave patterns slightly affected the yarn angles. On the other hand, it was observed that the number of layers considerably affected the radial arc length and the radial length in wall thickness in the 3D circular woven structure. The interlacement on 3D plain, twill and satin circular woven structures resulted in axial crimp, circumferential crimp and radial crimp. The crimps in the 3D fully interlaced circular woven structures slightly depended on the types of weave pattern and the number of layers.
Keywords: Three-dimensional fully interlaced preform; three-dimensional plain circular preform; three-dimensional twill circular preform; three-dimensional satin circular preform; radial crimp; circumferential and axial crimps